The Two Decades of Privatization in Polish Higher Education. Cost-Sharing, Equity, and Access - Kwiek, Marek (My University, 2009)
The general theme of coping with financial austerity has been prominent in thinking about the future of public higher education over the last two decades. Such thinking is often accompanied by a related theme in the future of public services generally—that of privatization. The generally tight fiscal environment for public services, including higher education, has not relaxed and, in many countries, will predictably intensify into a "pervasive condition of austerity" (Johnstone) or an environment of "permanent austerity" (Pierson). In European transition countries (including in new European Union member states), the solutions suggested for higher education systems increasingly include references to such notions as academic entrepreneurialism in teaching, research, and third mission activities, the need for academic institutions to become financially self-reliant, and cost-sharing in the form or introducing or increasing tuition fees accompanied by more student loans but fewer student scholarships, etc. Other commonly proposed strategies include heavier workloads for academics, larger class sizes, and contracts for faculty instead of tenure.
Keywords: cost-sharing; fees; Polish higher education; Polish universities; Poland; Central Europe; postcommunism; private sector; privatization; university reforms; reforming higher education; private sector growth; Daniel C. Levy; D. Bruce Johnstone; marketization; austerity; public policy; educational policy; public services; public sector; welfare state; welfare reforms